ANALISIS PENGARUH DISTRESS RISK, SIZE, BOOK TO MARKET, DAN MOMENTUM TERHADAP RETURN SAHAM (Studi pada Perusahaan Sektor Industri Dasar dan Industri Barang Konsumsi periode 2009-2014) - Pramusinta, Winda Safitri; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2016)
This research aims to analyze the influence of distress risk, size, book to market, and momentum toward stock return and to know the O-score prediction model in stock return of basic industry sector and consumer goods industry sector in Indonesia. Case study on basic industry sector and consumer goods industry sector in Indonesia Stock Exchange in period 2009-2014.Research population used isÂ basic industry sector and consumer goods industry sector in Indonesia in period 2009-2014. Taken samples of the all-purpose 32 firms by using porposive sampling method. The data used in this study were obtained from the Indonesia Capital Market Directory (ICMD), Yahoo Finance, Bloomberg, and www.idx.com 2009-2014. Analysis technique used is Ordinary Least Square (OLS) Regression, statistical t-test and classic assumption test that includes a test of normality test, multicollinearity test, heteroskedastisitas test, autocorrelation test.The result shows in bacis industry sector that distress risk and size has positive effect but not significant with stock return, book to market has negative effect but not significant with stock return, and momentum has positive effect and significant with stock return. The result of regression estimation show the ability of model prediction is 17.7% while the remaining 82.3% influenced by other factors outside the model.Moreover, in consumer goods industry sector shows that distress risk and size has positive effect but not significant with stock return, book to market has negative effect but not significant with stock return, and momentum has positiveeffect and significant with stock return. The result of regression estimation show the ability of model prediction is 17.7% while the remaining 82.3% influenced by other factors outside the model.Chow test indicated that there was no any difference on regression model between basic industry sector and consumer goods industry sectorÂ in Indonesia in period 2009-2014. The chow test shows that F value was lower than F table, that was 1.341189 > 10.127.